Causal relationships between gut microbiota and programmed cell death protein 1/programmed cell death-ligand 1: A bidirectional Mendelian randomization study - Huang, Yu-Feng; Zhang, Wei-Ming; Wei, Zhi-Song; Huang, Huan; Mo, Qi-Yan; Shi, Dan-Li; Han, Lu; Han, Yu-Yuan; Nong, Si-Kai; Lin, Guo-Xiang (Frontiers in Immunology, 2023)
Abstract Background: Multiple clinical studies indicate that the gut microbiota influences the effects of immune checkpoint blockade(ICB) therapy by PD-1/PD-L1 inhibitors, but their causal direction is still unclear. Because of numerous confounders, many microbes related to PD-1/PD-L1 have not been identified in the previous study. This study aims to determine the causal relationship between microbiota and PD-1/PD-L1 and further find possible biomarkers for ICB therapy. Method: We use bidirectional two-sample Mendelian randomization with two different thresholds to explore the potential causal relationship between microbiota and PD-1/PD-L1, further using species-level microbia GWAS to verify the result. Result: In the primary forward analysis, genus_Holdemanella showed a negative correlation with PD-1[βIVW=-0.25; 95% CI(-0.43 to -0.07); PFDR = 0.028], genus_Prevotella9 showed a positive correlation with PD-1 [βIVW=0.2; 95%CI(0.1 to 0.4); PFDR = 0.027]. the order_Rhodospirillales [βIVW=0.2; 95% CI(0.1 to 0.4); PFDR =0.044], family_Rhodospirillaceae [βIVW=0.2; 95%CI (0 to 0.4); PFDR = 0.032], genus_Ruminococcaceae_UCG005 [βIVW=0.29; 95%CI(0.08 to 0.5); PFDR=0.028], genus_Ruminococcus_gnavus_group [βIVW=0.22; 95%CI(0.05 to 0.4); PFDR =0.029 ] and genus_Coprococcus_2 [βIVW=0.4; 95%CI(0.1 to 0.6); PFDR =0.018 ] were positively correlated with PD-L1; the phylum_Firmicutes [βIVW=-0.3; 95%CI(-0.4 to -0.1); PFDR =0.031], family_ClostridialesvadinBB60group [βIVW= -0.31; 95%CI(-0.5 to -0.11), PFDR =0.008 ], family_Ruminococcaceae [βIVW=-0.33; 95%CI(-0.58 to -0.07); PFDR =0.049], genus_Ruminococcaceae_UCG014 [βIVW=-0.35; 95%CI(-0.57 to -0.13); PFDR =0.006] were negatively correlated with PD-L1. The one significant species in the further analysis is species_Parabacteroides_unclassified [βIVW=0.2; 95%CI(0 - 0.4); PFDR =0.029 ]. Heterogeneity (P>0.05) and pleiotropy (P>0.05) analysis confirmed the robustness of MR results. Conclusions: Overall, we demonstrated the potential causal relationships between the microbiomes and PD-1/PD-L1, including some genera lacking similar reports. This study expands the possibility of antineoplastic and immunotherapy.